The answer is 4 squared minus 2 squared as 4 squared is 16 minus 2 squared, which is 4, gives you 12 as an answer.
The square root of 28 minus the squared root of 7 =±2.64575131
The Answer is 1 coz, 1-Tan squarex = Cot square X. So cot square x divided cot square x is equal to 1
(x squared plus the square root of 2) times (x squared minus the square root of 2).
4 squared minus 2 squared equals 12
square root of 8
B squared equals c squared minus a squared then to find B take the square root of you answer for b squared
5 squared is 25 4 squared is 16 25-16= 9 the square root of 9 is 3.
X= plus or minus 1
Yes and x = 2+square root of 6 or x = 2-square root of 6
still 1The square root of 1 is plus or minus 1. √1 = ± 1 The reason is that 12 = 1 and -12 = 1. (Either 1 squared or minus 1 squared equals one.)
Complete the square or use the quadratic formula.
If x squared -10 = 0 then x = the square root of 10
the integral of the square-root of (x-1)2 = x2/2 - x + C
Two plus 3 minus 2 times 1 squared plus 4 times 16 squared minus 4 times 2 is equal to 1,019.
X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12
The square root of 25a squared is 5a. The square root of 16 is 4.So the answer is (5a+4)(5a-4)
the square root of b squared minus 4 times a times c
2m^2 - 8 -First you should factor out a two. --> 2(m^2-4) -You now have something squared minus something else squared; You have m squared minus 2 squared. Whenever you have something squared minus something squared as you do in this case, there is a simple rule to remember: You can reduce that expression into the quantity of the square root of the first number or variable plus the square root of the second number or variable Times the quantity of the square root of the first number or variable minus the second number or variable squared. --> In the case of your expression: ----> 2(m+2)(m-2)<-----
The square root of minus 8 is equal to the square root of 8 times the square root of minus 1, or 2.8284i.
a2 + 62 = 122 a2 + 62 - 62 = 122 - 62 a2 = 144 - 36 a2 = 108 taking the square root of each side, we get a equal plus or minus the square root of 108, or plus or minus 6 times the square root of 3.
x equals negative b plus or minus the square root of b squared minus 4bc over 2a
negative b plus or minus the square root of b squared minus 4AC all over 2 A